Polypropylene microfibers with a filler in the nanostate - Tsebrenko, Mariya; Rezanova, Victoriya; Tsebrenko, Irina (Publishing House of Lviv Polytechnic National University, 2010)
The physico-chemical regularities of polypropylene microfibers obtained via processing polypropylene/copolyamide (PP/CPA) mixture melts filled with nanosilicas have been investigated. It has been shown that the chemical nature of silica functional groups affects the viscosity of PP/CPA melts. In spite of the solid state of additives the filling effect does not occur or reveals weakly. Silicas do not prevent the polypropylene fiber-forming in a copolyamide matrix but improve it. This is explained by the stabilizing action of silica additives on PP liquid streams. Nanofilled polypropylenemicrofibers with diameters 0.30–0.15 мm have been obtained. Досліджені фізико-хімічні закономірності одержання поліпропіленових мікроволокон шляхом перероблення розплавів сумішей поліпропілен/співполіамід (ПП/СПА), наповнених нанокремнеземами. Показано, що хімічна природа функцій них груп кремнеземів впливає на в’язкість розплавів ПП/СПА. Незважаючи на твердий стан добавки, ефект наповнення не має місця або проявляється слабо. Кремнеземи не перешкоджають волокноутворенню поліпропілену, а покращують його. Останнє пояснюється cтабілізуючою дією нанодобавки на рідкі струмені ПП. Одержані поліпропіленові мікроволокна з діаметрами 0,30–0,15 мкм, наповнені нанокремнеземами.
Поліпропіленові мікроволокна з наповнювачем в наностані
Keywords: polymer mixtures; viscosity; microfibers; silica; nanoadditives; interfacial tension; суміші полімерів; в’язкість; мікроволокна; нанодобавки; міжфазний натяг; кремнезем